Addition of anti-TIM3 or anti-TIGIT Antibodies to anti-PD1 Blockade Augments Human T cell Adoptive Cell Transfer. (1st January 2021) - Martinez, Marina; Kim, Soyeon; St. Jean, Naomi; O'Brien, Shaun; Lian, Lurong; Sun, Jing; Verona, Raluca I.; Moon, Edmund
ABSTRACT: PD1 blockade to reinvigorate T cells has become part of standard of care for patients with NSCLC across disease stages. However, the majority of patients still do not respond. One potential mechanism of resistance is increased expression of other checkpoint inhibitory molecules on T cells leading to their suppression; however, this phenomenon has not been well studied in tumor-reactive, human T cells. The purpose of this study was to evaluate this compensatory mechanism in a novel model using human effector T cells infiltrating and reactive against human lung cancer. Immunodeficient mice with flank tumors established from a human lung cancer cell line expressing the NYESO1 antigen were treated with activated human T cells expressing a TCR reactive to NYESO1 (Ly95) with or without anti-PD1 alone and with combinations of anti-PD1 plus anti-TIM3 or anti-TIGIT. A month later, the effect on tumor growth and the phenotype and ex vivo function of the TILs were analyzed. Anti-PD1 and Ly95 T cells led to greater tumor control than Ly95 T cells alone; however, tumors continued to grow. The ex-vivo function of PD1-blocked Ly95 TILs was suppressed and was associated with increased T cell expression of TIM3/TIGIT. Administering combinatorial blockade of PD1+ TIM3 or PD1+ TIGIT with Ly95 T cells led to greater tumor control than blocking PD1 alone. In our model, PD1 blockade was suboptimally therapeutic alone. The effect of TIM3 and TIGIT was upregulated on T cells in response to PD1 blockade and anti-tumor activity could be enhanced when these inhibitory receptors were also blocked with antibodies in combination with anti-PD1 therapy.